Revised CRISM spectral parameters and summary products based on the currently detected mineral diversity on Mars. Issue 6 (26th June 2014) - Viviano‐Beck, Christina E.; Seelos, Frank P.; Murchie, Scott L.; Kahn, Eliezer G.; Seelos, Kimberley D.; Taylor, Howard W.; Taylor, Kelly; Ehlmann, Bethany L.; Wisemann, Sandra M.; Mustard, John F.; Morgan, M. Frank
Abstract The investigation of hyperspectral data from the Mars Reconnaissance Orbiter Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) and the Observatoire pour la Minéralogie, L'Eau, les Glaces et l'Activitié (OMEGA) on Mars Express has revealed an increasingly diverse suite of minerals present on the Martian surface. A revised set of 60 spectral parameters derived from corrected spectral reflectance at key wavelengths in CRISM targeted observations and designed to capture the known diversity of surface mineralogy on Mars is presented here as "summary products." Some of the summary products have strong heritage to OMEGA spectral parameter calculations; this paper also presents newly derived parameters that highlight locations with more recently discovered spectral signatures. Type locations for the diversity of currently identified mineral spectral signatures have been compiled into a library presented in this work. Our analysis indicates that the revised set of summary products captures the known spectral diversity of the surface, and successfully highlights and differentiates between locations with differing spectral signatures. The revised spectral parameter calculations and related products provide a useful tool for scientific interpretation and for future mission landing site selection and operations.